2011
DOI: 10.1071/rd10133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal age on mitochondrial DNA copy number, ATP content and IVF outcome of bovine oocytes

Abstract: The primary aim of the present study was to examine the effect of maternal age (in months) on mitochondrial DNA copy number (Mt number), ATP content and IVF outcome of bovine oocytes. We also compared the Mt number of oocytes with fertilisation outcome and ATP content. Oocytes were collected from cows aged 20-204 months and the Mt number was determined by real-time polymerase chain reaction. The Mt number in immature and mature oocytes was determined to be 368,118 and 807,794, respectively; the ATP content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 46 publications
9
139
3
2
Order By: Relevance
“…In previous reports, oocytes from cows aged more than 120 months old had some abnormalities compared with those from young cows aged 25-50 months [9,10,28]. In the present study, cows aged more than 120 months were defined as aged cows and cows aged 20-35 months were defined as young cows.…”
Section: Definition Of Aged and Young Cowsmentioning
confidence: 70%
See 2 more Smart Citations
“…In previous reports, oocytes from cows aged more than 120 months old had some abnormalities compared with those from young cows aged 25-50 months [9,10,28]. In the present study, cows aged more than 120 months were defined as aged cows and cows aged 20-35 months were defined as young cows.…”
Section: Definition Of Aged and Young Cowsmentioning
confidence: 70%
“…These results suggest that in vivo development of EAFs is suspended after some developmental progression of the EAFs and the oocyte growth from EAF to AF is impaired in aged cows; this stagnation may be related to the gene expression profiles in granulosa cells of aged cows. Oocytes collected from antral follicles (3-6 mm in diameter) of aged cows had evidently lower ability to mature, fertilize, cleave and develop into the blastocyst stage [9][10][11]. However, there are no reports regarding the in vitro developmental competence of bovine oocytes of EAFs of aged cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oocyte number used for Mt number assays was based on previous reports that demonstrated that the Mt number determined from ten oocytes collected from a donor closely resembles the Mt number obtained by another group of ten cohort oocytes collected from the same donor (Sato et al 2014). Oocytes were denuded from granulosa cells and the DNA extraction and PCR protocols procedures were performed according to previously described methods (Iwata et al 2011). The Mt number was determined by performing real-time PCR using a Rotor-Gene 6500 real-time rotary analyser (Corbett Research, Mortlake, NSW, Australia) with the primers 5 0 -CGAGAAAGCACTTTCCAAGG-3 0 (forward) and 5 0 -CTAATTCGGGTGTTGGTGCT-3 0 (reverse) and Bio-Rad Ssofast-TM EvaGreen Supermix (Bio Rad).…”
Section: Mitochondrial Dna Copy Number Determinationmentioning
confidence: 99%
“…For example, maturation of oocytes from young (21-89 months) bovine donors resulted in a mean increase in mitochondrial copy number and ATP content, whereas maturation of oocytes from 'aged' (.89 months) bovine donors led to a decrease in both parameters (Iwata et al 2011). Similarly in vitro maturation (IVM) of oocytes retrieved from older mares ($12 years) led to a significant decrease in mitochondrial copy number that was not seen in younger mares (,12 years; Rambags et al 2014).…”
Section: Introductionmentioning
confidence: 99%